2012
DOI: 10.1021/nl301912f
|View full text |Cite
|
Sign up to set email alerts
|

Template-Free Preparation of Crystalline Ge Nanowire Film Electrodes via an Electrochemical Liquid–Liquid–Solid Process in Water at Ambient Pressure and Temperature for Energy Storage

Abstract: The direct electrodeposition of crystalline germanium (Ge) nanowire film electrodes from an aqueous solution of dissolved GeO(2) using discrete 'flux' nanoparticles capable of dissolving Ge(s) has been demonstrated. Electrodeposition of Ge at inert electrode substrates decorated with small (<100 nm), discrete indium (In) nanoparticles resulted in crystalline Ge nanowire films with definable nanowire diameters and densities without the need for a physical or chemical template. The Ge nanowires exhibited strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 38 publications
8
77
2
5
Order By: Relevance
“…Таким образом, отсутствие роста на Sn и его наличие на In, а также сопоставление полученных нами экспериментальных ре-зультатов с результатами работ [12,13,15] указывают на то, что основополагающую роль для синтеза нитевидных нанокристаллов Ge из водного раствора является нали-чие частиц металла в жидком состоянии.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Таким образом, отсутствие роста на Sn и его наличие на In, а также сопоставление полученных нами экспериментальных ре-зультатов с результатами работ [12,13,15] указывают на то, что основополагающую роль для синтеза нитевидных нанокристаллов Ge из водного раствора является нали-чие частиц металла в жидком состоянии.…”
Section: Discussionunclassified
“…• C. Так, в работе [15] возможность роста нитевидных структур германия из водных растворов с использованием частиц In с размера-ми, не превышающими 100 нм (температура плавления объемного In составляет ∼ 156.6…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Vapour and liquid-based growth of Ge nanowires consists of any method where the Ge precursor is in either vapour and liquid form and include techniques such as chemical vapour deposition (CVD) [45][46][47][48][49][50] , metal-organic chemical vapour deposition (MOCVD) 51 52 , molecular beam epitaxy [53][54][55] , template methods 56,57 and various evaporation methods such as electron beam evaporation 58,59 and thermal evaporation 60,61 . Alternatively, liquid/solution (see figure 1) 14,52,[62][63][64][65][66][67] and SCF [68][69][70][71][72] based methods involve the introduction of precursors in liquid and supercritical media respectively. The key mechanism involved in most of these processes is analogous to the VLS mechanism first proposed by…”
Section: Seeded Growth In Vapour and Liquid Mediamentioning
confidence: 99%
“…[26][27][28][29][30][31] Previously studies have demonstrated that decreasing the Ge particle size into the nanometer range could alleviate the stress produced during Li uptake and release processes and suppress the tendency of the nanostructure to fracture. [32][33][34][35] Moreover, the nanostructure can facilitate the diffusion of Li ion, resulting in high rate capability. [36][37][38][39] However, the cycling performance remains unsatisfactory because the Ge nanoparticles aggregate during cycling.…”
Section: Introductionmentioning
confidence: 99%